TEKNIK PERANCANGAN KONTRAK - Tom Alfa Samuel Reumi; Tri Yanuaria (JURNAL PENGABDIAN PAPUA, 2021)
This community service aims to provide a social services to a community named Papua Preneur. The member of Papua Preneur were young Papuan running small business in Jayapura City and categorized as poor and vulnerable business man. The reason behind this avtivity was because, most of those business man had lack of knowledge regarding how to make Collaboration Agreement or MOU with business partner which somehow impact to ther business. This activity were conducted throughout 5 months using zoom application. The subject of training were start from planning, training, assesment, practicing (how to make a good colaboration agreement). Hopefully through this assesment, the member of Papua Preneur could understand and finally can make colaboration agreement or MoU by themself. Keywords: Papua preneur; business; business man; Jayapura